Negotiating Girl-led Advocacy: Addressing Early and Forced Marriage in South Africa. Issue 2 (1st June 2020) - Haffejee, Sadiyya; Treffry-Goatley, Astrid; Wiebesiek, Lisa; Mkhize, Nkonzo
Abstract: Increasingly, researchers and policymakers recognize the ability of girls to effect social change in their daily lives. Scholars working across diverse settings also acknowledge the key influence of individual, family, and societal structures on such activism. Drawing on our work with girls in a participatory visual research project in a rural community in South Africa, we consider examples of partnership and collaboration between the adult research team and the young participants. We highlight their agency in mobilizing adults to partner and support community and policy change to address traditional practices of early and forced marriage in this setting. We conclude that collaborative engagement with adults as partners can support activism and advocacy led by girls in contexts of traditional leadership.